The Effects Of Perceived Usefulness, Perceived Ease Of Use, And Trust On The Intention To Use Alfagift E-Grocery - Isnurratna Sigita Hasanah; Roekhudin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The rapid development of technology in Indonesia has transformed consumer behavior, with more people turning to digital platforms for shopping. As one of the country's largest retail companies, Alfamart has responded to this shift by developing Alfagift e-grocery. This study aims to analyze the factors influencing the intention of Malang City residents to use Alfagift. The Technology Acceptance Model (TAM) was adopted with an additional variable, trust. Using purposive sampling, 138 Malang City residents were selected as the respondents, and the data were collected through Google Forms questionnaires. The results of the analysis indicate that perceived usefulness, perceived ease of use, and trust positively influence the intention to use Alfagift e-grocery. This study provides an empirical contribution to understanding the influence of the Technology Acceptance Model, particularly perceived usefulness, perceived ease of use, and trust, on the adoption of e-grocery technology.